The Development and Validation of Sexual Health Education Needs Assessment Questionnaire of Iranian Engaged couples: - Bostani khalesi, Zahra; Simbar, Masoumeh; Azin, Seyed Ali (Galen Medical Journal, 2017)
Background: Knowledge about sexual health is one of the basic needs of young couples. The present study aimed to develop and validate the Sexual Health Education Needs Assessment Questionnaire (SHENAQ). Materials and Methods: This study was a sequential exploratoÂry mixed method. In the qualitative phase, In-depth interviews were conducted with 38 enÂgaged and married men and women and 9 key informants. After a literature review, in the quantitative phase, validity properties of the SHENAQ were assessed. Results: Sexual health education needs consists of 4 themes â€œSuitable content for education â€œ,â€ Characteristics of competent educatorsâ€, â€œAppropriate technologies in educationâ€ andâ€ Educational convenient featuresâ€. The content validity ratio (CVR) and content validity index (CVI) of the instrument were 0.91 and0.83 respectively. SHENAQ was designed with 46 items. The instrumentâ€™s inÂternal consistency was confirmed by alpha coefficient 0.863 and stability assessment through the test-retest was 0.824. Conclusion: SHENAQ is culturally sensitive with satisfactory vaÂlidity and reliability and could be used to increase the effectiveness of premarital education. [GMJ.2017;6(4):302-11] DOI: 10.22086/gmj.v6i4.854